Seasonal Guild Variation of a Bat Assemblage in an Agricultural Landscape of a Tropical Dry Forest of Costa Rica - Ramírez-Vargas, Marco A. (2019)
In Costa Rica, the tropical dry forest is restricted into the North Pacific, being one of the few remnants of the Mesoamerican dry forest. This forest presents remarkable climatic variation throughout the year, especially in precipitation. This variation makes it necessary for the animals that live here to adapt according mainly to food availability. We analyze a bat assemblage in terms of its species richness and guild composition in an agro dry forest landscape. We describe how the presence, abundance and guilds of different bat species varies through time and closely relates to rainfall pattern, distinctly affecting nectarivorous, frugivorous, insectivorous or hematophagous. We propose that the species that make up the assemblage of bats at this site probably make local movements periodically, using the area only temporarily. We emphasize that, given the movement of species during the year, the maintenance of natural elements such as forest patches and wetlands within ago-landscapes is mandatory in order to achieve a regional conservation strategies.